Therapeutic Hypothermia in Brain Injury - Sadaka, Farid (IntechOpen, 2013)
This book describes the evidence behind the application of Therapeutic Hypothermia on patients with injury to the brain and spinal cord, that includes ischemia reperfusion after cardiac arrest or asphyxiation, traumatic brain injury, acute ischemic stroke, hemorrhagic stroke, refractory intracranial hypertension, cerebral edema in acute liver failure, subarachnoid hemorrhage, as well as spinal cord injury. This book discusses the mechanisms by which therapeutic hypothermia can mitigate the pathophysiologies responsible for secondary brain injury, and provides information to help guide this treatment with regard to timing, depth, duration, and management of side-effects. The book also discusses the methods and technologies used to induce and maintain therapeutic hypothermia. It also describes how hypothermia can influence the ability to prognosticate these injured patients and provides grounds for future directions in the application of and research with therapeutic hypothermia.